2020
DOI: 10.1080/07391102.2020.1787227
|View full text |Cite
|
Sign up to set email alerts
|

Epitope based peptide vaccine against SARS-COV2: an immune-informatics approach

Abstract: World is witnessing exponential growth of SARS-CoV2 and fatal outcomes of COVID 19 has proved its pandemic potential already by claiming more than 3 lakhs deaths globally. If not controlled, this ongoing pandemic can cause irreparable socio-economic and psychological impact worldwide. Therefore a safe and effective vaccine against COVID 19 is exigent. Recent advances in immunoinformatics approaches could potentially decline the attrition rate and accelerate the process of vaccine development in these unprecede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 44 publications
0
40
0
Order By: Relevance
“…Apart from this, b-defensin interact with the immune receptors such as TLRs or CCR6 and induces innate and adaptive immune responses (Lei et al, 2019). It is used as an adjuvant in the construction of several vaccines by Immunoinformatics approach (Ali et al, 2017;Bhatnager et al, 2020;Dong et al, 2020;Narula et al, 2018). Apart from b-defensin, PADRE (pan DR epitope) sequence was also included in the vaccine construct to increase the immunogenicity of the vaccine construct as well as to enhance the T-cell help (Alexander et al, 2000;Sarkar et al, 2020;Wu et al, 2010).…”
Section: Design Of Vaccine Constructmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from this, b-defensin interact with the immune receptors such as TLRs or CCR6 and induces innate and adaptive immune responses (Lei et al, 2019). It is used as an adjuvant in the construction of several vaccines by Immunoinformatics approach (Ali et al, 2017;Bhatnager et al, 2020;Dong et al, 2020;Narula et al, 2018). Apart from b-defensin, PADRE (pan DR epitope) sequence was also included in the vaccine construct to increase the immunogenicity of the vaccine construct as well as to enhance the T-cell help (Alexander et al, 2000;Sarkar et al, 2020;Wu et al, 2010).…”
Section: Design Of Vaccine Constructmentioning
confidence: 99%
“…The whole genome sequence of the SARS-CoV2 is made available in the public domain by next generation sequencing. This enabled the design of several multi-epitope in silico vaccine candidates targeting different structural and nonstructural proteins of the SARS-CoV2 (Bhatnager et al, 2020;Bhattacharya et al, 2020;Devi & Chaitanya, 2020;Dong et al, 2020;Enayatkhani et al, 2020;Kar et al, 2020;Lizbeth et al, 2020;Peele et al, 2020;Samad et al, 2020). In the present study, we aimed to design a novel multi-epitope vaccine targeting membrane glycoprotein by immunoinformatics approach.…”
Section: Introductionmentioning
confidence: 99%
“…105,106 These three TLRs were used in designing in previous bioinformatic-based vaccines against SARS-CoV-2. 30,107,108 The results of docking analysis showed the vaccine protein properly interacts with TLR3, 5, and 8. In addition, docking results of the vaccine and ACE-2 reveal the RBD epitopes of the vaccine can efficiently interact with ACE-2.…”
Section: Dovepressmentioning
confidence: 99%
“… 12 Recent efforts for designing epitope-based peptide vaccine based on an immune-informatics approach showed that a multivalent subunit vaccine targeting S2 subunit of SARS-CoV-2 S glycoprotein might have potential to activate innate and adaptive immune responses. 13 In addition, the receptor binding domain (RBD) of the S protein of SARS-CoV-2 appears to be potentially useful in the serological diagnostic assays for COVID-19 patients. 14 Furthermore, the immune responses to S-RBD binding antibodies exhibited a correlation with neutralizing capacity, suggesting a potential COVID-19 immunity.…”
Section: Introductionmentioning
confidence: 99%